SCIENCE, ART, AND AESTHETICS: AN INTERDISCIPLINARY APPROACH TO ABSTRACT REASONING - Hammer, Samuel (European Scientific Journal, ESJ, 2014)
Scientists and artists share methodologies that are common to both practices. From a behavioral perspective, both scientists and artists utilize observation, contemplation, reflection, and serious play to interpret abstract environmental signals. Abstractions are interpreted through an aesthetic, an algorithm for problem solving, which is the basis for scientific and artistic modeling. Models vary in their presentation, comprising works of art, formulas, theories, or diagrams but all of them have one thing in common: they communicate abstract ideas. In an interdisciplinary approach to teaching undergraduate science, students mimic the behaviors of scientists and artists to engage in complex biological problems. As students observe, contemplate, reflect, and play they visualize and make sense of abstractions that represent cellular, molecular, and evolutionary biology. By reflecting on their own practice of model-building, students achieve an enhanced understanding of their personal aesthetic, the tool they use for problem solving, which is key to abstract reasoning and critical thinking.